Stellar initial mass function over a range of redshifts - Riaz, Rafeel; Schleicher, Dominik R. G.; Vanaverbeke, Siegfried; Klessen, Ralf S. (Astronomische Nachrichten, 2021)
The stellar Initial Mass Function (IMF) seems to be close to universal in the local star-forming regions. However, this quantity of a newborn stellar population responds differently at gas metallicities Z ∼ Z⊙ than Z = 0. A view on the cosmic star formation history suggests that the cooling agents in the gas vary both in their types and molecular abundances. For instance, in the primordial gas environment, the gas temperature can be higher by a factor of 30 as compared to the present day. Stellar radiation feedback and cosmic microwave background (CMB) radiation may even contribute toward increasing the floor temperature of the star-forming gas which subsequently can leave profound impacts on the IMF. We present the contribution of the radiation sources toward the thermodynamical evolution of the Jeans unstable gas cloud which experiences fragmentation and mass accretion. We find evidence which suggests that the latter becomes the dominant process for star formation efficiencies (SFE) above 5-7%, thus increasing the average mass of the stars. We focus on the isolated and binary stellar configurations emerging during the gas collapse. The binary fraction on average remains 0.476 and contributes significantly toward the total SFE of 15%.